Is Physical Activity Related to Depression and Anxiety among Adults? Observations from a Noncommunicable Disease Screening Clinic in North India - Madhur Verma; Amandeep Kaur; Ankush Upneja; Preeti Dhoat; Jitender Aneja; Rakesh Kakkar (Indian Journal of Community Medicine)
Background: Physical activity (PA) offers innumerable benefits and is a promising intervention against common mental disorders, such as depression and anxiety. We examined the association between PA and depression or anxiety in adults. Materials and Methods: A study was conducted between March 2021 and August 2022 using a cross-sectional study design. We recruited 334 participants >40 years of age from the noncommunicable disease (NCD) screening clinic of a tertiary care institute in North India. Health-enhancing PA (HEPA) was estimated using the International Physical Activity Questionnaire (IPAQ), while depression and anxiety were screened using the 9-item Patient Health Questionnaire (PHQ-9) and 7-item Generalized Anxiety Disorder scales. Bivariate and univariate analyses were performed using Statistical Package for the Social Sciences (SPSS) version 21 to depict our results. Results: Engagement in HEPA was 23.4%. The HEPA depicted significant socioeconomic disparities. The mean total cholesterol and triglyceride levels were considerably higher in the HEPA active group, despite having lower GAD-7 and PHQ-9 scale scores. The prevalence of depressive and anxiety symptoms was 59.0% and 13.4%. PA depicted better odds against depression but not against anxiety symptoms. Conclusions: Low HEPA engagement in adults is a matter of concern, and it is high time we look beyond NCDs toward the risk factors. It is essential to incorporate PA counseling universally and not be restricted to a particular clinical department to realize its full potential in restraining the growing NCD burden.